Outcomes of Concurrent Functional Endoscopic Sinus Surgery and Rhinoplasty: A Meta-analysis. Issue 5 (September 2021) - Bitner, Benjamin F.; Prasad, Karthik R.; Goshtasbi, Khodayar; Dunn, Brandyn S.; Kuan, Edward C.
Introduction: Chronic rhinosinusitis (CRS) and functional nasal airway obstruction are common but distinct medical problems which affect quality of life. In certain instances, patients often benefit from concomitant functional septorhinoplasty, or elect for cosmetic rhinoplasty, in addition to functional endoscopic sinus surgery (FESS) and prefer combining procedures. Determining outcomes of combined surgery is important when discussing risks and benefits with patients. Methods: A thorough literature search of articles published in PubMed, Ovid MEDLINE, and Cochrane databases. Patients were categorized as either having FESS or rhinoplasty alone or combined. Binary random-effects models were applied to calculate odds ratios (ORs) for outcomes including complications, recurrence, and satisfaction. Results: Of the 55 screened articles, 6 were included in the analysis, and of these, 6 (405 patients), 2 (90 patients), 4 (290 patients), and 3 (190 patients) provided data for postoperative complications, recurrence of CRS symptoms, revision rates, and patient satisfaction, respectively. Major complications were observed in 11 (5.8%) total combined cases, 0 (0%) FESS cases, and 6 (3.5%) rhinoplasty cases with no statistical difference between combined cases and rhinoplasties (OR 1.37, 95% CI 0.45–4.16, p = 0.58). Recurrence of CRS symptoms was noted in 35.6% combined cases and 28.9% FESS cases (OR 1.42, 95% CI 0.55–3.64, p = 0.47). There was no observed difference in revision rates between combined and isolated rhinoplasties (OR 1.00, 95% CI 0.43–2.32, p = 1). Lastly, 91.6% of patients were satisfied with results of combined cases compared to 87.4% of patients in standalone cases (OR 1.57, 95% CI 0.61–4.03, p = 0.35). Conclusion: Aggregate evidence demonstrates similar risk in complication rates in combined surgical cases compared to stand-alone rhinoplasty. There appears to be no significant difference in recurrence of symptoms, revision rates or patient satisfaction.